1982
DOI: 10.2134/agronj1982.00021962007400040014x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing Temperatures during Soybean Seed Maturation on Seed Quality1

Abstract: Soybean [Glycine max (L.) Merr.] seed produced from late maturing cultivars or following delayed planting of early maturing cultivars is often exposed to frost prior to maturation and harvest. Since little information is available regarding the effect of freezing temperatures on seed germination, freezing experiments were conducted with intact plants, and detached pods in controlled environmental chambers. Pods at three developmental stages (green, yellow, and brown) were exposed to temperatures of −2 to −12 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…These observations are in line with the previous reports about low temperature effects in chickpea (Nayyar et al. 2007) and other plant species (Judd et al. 1982, Egli et al.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are in line with the previous reports about low temperature effects in chickpea (Nayyar et al. 2007) and other plant species (Judd et al. 1982, Egli et al.…”
Section: Discussionsupporting
confidence: 93%
“…A curvilinear change in FPT occurred in both the embryo and endosperm tissue as seeds matured (Fig. 5B), which was similar to the pattern reported for soybean (Judd et al, 1982). Our data also are supported by the results of Fick (1989), who reported that corn embryo and endosperm FPT declined substantially as seed moisture decreased from 340 to 300 g kg −1 However, he evaluated only a very narrow range in SMC, which contributed little to our understanding of the FPT changes that occur throughout corn seed development.…”
Section: Discussionsupporting
confidence: 84%
“…Roberts and Ellis (1989) reported that the FPT for immature barley ( Hordeum vulgare L.) seeds was above −5°C between SMC of 350 and 500 g kg −1 Freezing point temperature declined as moisture content dropped below 350 g kg −1 A similar pattern was found for lettuce ( Lactuca sativa L.) seeds, except that FPT remained above −5°C until the moisture was below 200 g kg −1 Fick (1989) found a significant difference in FPT between corn seed harvested at 610 g kg −1 (−1.2°C) and 480 g kg −1 (−1.6°C). Judd et al (1982) reported a curvilinear decrease in FPT of soybean [ Glycine max (L.) Merr.)] seed as seed moisture decreased with FPT ranging from −2.5°C at 600 g kg −1 SMC to −20°C at 300 g kg −1 The ice–liquid phase transition temperatures in mature, rehydrated soybean cotyledons exhibited a linear decline from −36°C at ≈300 g kg −1 to −43°C at ≈50 g kg −1 using differential scanning calorimetry (Vertucci, 1989).…”
mentioning
confidence: 99%
“…Neal (1961) reported cold test germination was reduced for inbred corn seed (SMC >250 g kg −1 ) when exposed to −6°C for 4 h, however germination was not reported. Judd et al (1982) used the AA vigor test to determine the effects of freezing injury on soybean seed and found no differences in AA germination between control seed and those exposed to −2°C for up to 32 h. When the seed was frozen at lower temperatures (−7 or −12°C), AA germination was significantly reduced below the unfrozen control, however significant declines also occurred in standard germination.…”
mentioning
confidence: 99%
“…Our results suggest that a seed producer will have higher germination and vigor if they harvest immature seeds (#400 g kg 21 SMC) before the freezing event instead of after they are exposed to freezing temperatures. E XPOSURE of developing seeds to freezing temperatures decreases seed germination in many species: pea (Pisum sativum L.) (Vertucci, 1989), sunflower (Helianthus annuus L.) (Zimmerman and Zimmer, 1978), winter rape (Brassica napus L.) (Lardon and Triboi-Blondel, 1994), sorghum [Sorghum bicolor (L.) Muench] (Robbins and Porter, 1946), soybean [Glycine max (L.) Merrill] (Robbins and Porter, 1946;Judd et al, 1982;Vertucci, 1989;Osorio and McGee, 1992) and corn (Kiesselbach and Ratcliff, 1920;Goodsell, 1948;Rossman, 1949aRossman, , 1949bFick, 1989). The severity of germination loss was influenced by the interaction of three factors: seed maturity, the temperature to which seeds were exposed, and the duration of exposure.…”
mentioning
confidence: 99%